Linking bacterial community to aggregate fractions with organic amendments in a sandy soil. (25th July 2019) - Dai, Hongcui; Zang, Huadong; Zhao, Yingxing; Qian, Xin; Liu, Kaichang; Wang, Dong; Hao, Jinyu; Chen, Yuanquan; Sui, Peng
Abstract: Soil aggregates provide microhabitats for microorganisms. However, the bacterial communities within various aggregate size fractions under organic amendments have rarely been evaluated especially in sandy soils. A field experiment involving addition of biogas residue (BR), pig manure (PM), biochar (BC), and straw (ST) of a sandy soil was performed to determine the structure of the bacterial community in aggregate size fractions by using high‐throughput sequencing. We found that organic amendments change soil aggregate fractions and nutrient content, alter bacterial diversity and composition, and contribute to the predicted bacterial functions. The BR increased bacterial α‐diversity in <0.25‐mm aggregates. The Nitrospirae was abundant in almost all aggregate sizes, whereas the abundance of Actinobacteria decreased in most of aggregates following BR addition. The PM amendment primarily facilitated the growth of Bacteroidetes and inhibited the growth of Acidobacteria and Chloroflexi in 0.25‐ to 2‐mm aggregates, whereas bacterial α‐diversity was decreased in the >0.25‐mm aggregates. The BC treatment decreased the bacterial α‐diversity in the <0.25‐mm aggregates and the Gemmatimonadetes abundance in all <2‐mm aggregates, but the Actinobacteria abundance was significantly increased in the >0.053‐mm aggregates. Collectively, the effects of organic amendments on the bacterial community varied greatly depending on type of amendments and aggregate size. The BR supported highly diverse bacterial taxa in the <0.25‐mm aggregates, whereas it proliferated N cycling‐related bacteria in all aggregates. Our results highlight the links between bacterial community and aggregate size fractions in sandy soils depending on organic amendments.